Liver trauma: WSES 2020 guidelines - Federico Coccolini; Raul Coimbra; Carlos Ordonez; Yoram Kluger; Felipe Vega; Ernest E. Moore; Walt Biffl; Andrew Peitzman; Tal Horer; Fikri M. Abu-Zidan; Massimo Sartelli; Gustavo P. Fraga; et al. (World Journal of Emergency Surgery, 2020)
Abstract Liver injuries represent one of the most frequent life-threatening injuries in trauma patients. In determining the optimal management strategy, the anatomic injury, the hemodynamic status, and the associated injuries should be taken into consideration. Liver trauma approach may require non-operative or operative management with the intent to restore the homeostasis and the normal physiology. The management of liver trauma should be multidisciplinary including trauma surgeons, interventional radiologists, and emergency and ICU physicians. The aim of this paper is to present the World Society of Emergency Surgery (WSES) liver trauma management guidelines.